ATP Synthase Deficiency due to TMEM70 Mutation Leads to Ultrastructural Mitochondrial Degeneration and Is Amenable to Treatment. (13th October 2015) - Braczynski, Anne K.; Vlaho, Stefan; Müller, Klaus; Wittig, Ilka; Blank, Anna-Eva; Tews, Dominique S.; Drott, Ulrich; Kleinle, Stephanie; Abicht, Angela; Horvath, Rita; Plate, Karl H.; Stenzel, Werner; et al.
Abstract : TMEM70 is involved in the biogenesis of mitochondrial ATP synthase and mutations in the TMEM70 gene impair oxidative phosphorylation. Herein, we report on pathology and treatment of ATP synthase deficiency in four siblings. A consanguineous family of Roma (Gipsy) ethnic origin gave birth to 6 children of which 4 were affected presenting with dysmorphic features, failure to thrive, cardiomyopathy, metabolic crises, and 3-methylglutaconic aciduria as clinical symptoms. Genetic testing revealed a homozygous mutation (c.317-2A>G) in the TMEM70 gene. While light microscopy was unremarkable, ultrastructural investigation of muscle tissue revealed accumulation of swollen degenerated mitochondria with lipid crystalloid inclusions, cristae aggregation, and exocytosis of mitochondrial material. Biochemical analysis of mitochondrial complexes showed an almost complete ATP synthase deficiency. Despite harbouring the same mutation, the clinical outcome in the four siblings was different. Two children died within 60 h after birth; the other two had recurrent life-threatening metabolic crises but were successfully managed with supplementation of anaplerotic amino acids, lipids, and symptomatic treatment during metabolic crisis. In summary, TMEM70 mutations can cause distinct ultrastructural mitochondrial degeneration and almost complete deficiency of ATP synthase but are still amenable to treatment.